Charles Atlas. Edited by Lauren Wittels. Contributions by Charles Atlas, with the assistance of Johanna Fateman, Stuart Comer, Douglas Crimp, Douglas Dunn, Lia Gangitano. 2015. Munich, New York: Prestel, 303 pp, chiefly color screen stills. $75 hardcover. ISBN: 9783791381008 - Bukhari, Kyle (The International Journal of Screendance, 2019)
Review of Charles Atlas edited by Lauren Wittels.